P107 Prevalence of haemarthrosis and clinical impact on the musculoskeletal system in people with haemophilia in the United Kingdom: evaluation of UKHCDO and haemtrack patient reported data. (20th April 2020) - Wilkins, Richard A; Siddle, Heidi J; Chapman, Graham; Redmond, Anthony J; Xiang, Hau; Scott, Martin; Richards, Michael; Horn, Lishel; Palmer, Ben; Stephensen, David
Abstract: Background: Haemarthrosis whereby bleeding occurs within a joint is a significant feature of haemophilia. Despite the availability of prophylaxis clotting factor concentrates in the United Kingdom haemarthrosis is associated with worsening joint health and haemarthropathy in people with severe haemophilia. The ankle joint has been identified as the most affected joint followed by the knee and elbow. Whilst annual joint bleed rates (AJBR) are commonly reported in haemophilia research, bleed rates in individual affected joints and joint health status in paediatric and adult patients is yet to be established. Methods: In 2018, paediatric (<18 years) and adult (≥18 years) patients with severe non-inhibitor haemophilia A and B registered with the United Kingdom Haemophilia Centres Doctors Organisation (UKHCDO) National haemophilia Database (NHD) were evaluated for haemarthrosis prevalence and associated joint health. Fully itemised Haemophilia Joint Health Scores (HJHS) were obtained from NHD records in combination with AJBR from Haemtrack (HT) compliant patients. Haemarthrosis prevalence and AJBR were reported as a total and for individual joints (ankles, knees and elbows). Results: During 2018, 2233 individuals were identified; 273 reported ≥75% simultaneous HT compliance and electronic fully itemised HJHS data. The median (range) age of children is 10 (6-14) years and adults 40 (25-51) years. The joint bleed prevalence of haemophilia A and B in children is 33% and 47% respectively, and in adults 42% and 60% respectively. In children with haemophilia A (n = 80) the knee (data) was the most common site of bleeding. In haemophilia A adults (n = 157) the ankle and elbow were equally affected. In haemophilia B children (n = 17) and adults (n = 19) the elbow was the most prevalent site. Total HJHS scores in children with haemophilia A and B were 0.00 (1.00 SD) and 0.40 (0.90 SD) respectively. Total HJHS scores in adults with haemophilia A and B were 21.20 (16.80 SD) and 15.40 (15.10 SD) respectively. Mean HJHS scores itemised by joint were higher in adults compared with children. In children with haemophilia A and haemophilia B, mean (3.80) and median (4.00) scores for the ankle joint were higher than for the knee (2.90 and 1.00) and elbow joint (3.30 and 1.00). Conclusion: Whilst there are limitations to this self-select subset of individuals with severe haemophilia, t he prevalence of haemarthrosis is evenly distributed in all adult joints with a trend towards the knee in paediatrics. Despite prophylaxis 30% of children and 60% adults still reported bleeding over a 12-month period. Irrespective of the prevalence of joint bleeds in children with haemophilia the HJHS does not appear to be clinically sensitive enough to detect changes in joint health. Adults deemed adherent with prophylaxis and haemtrack still demonstrate worsening HJHS scores despite a low AJBR. Disclosures: R.A. Wilkins Grants/research support; Funded by the National Institute for Health Research. H.J. Siddle Grants/research support; Funded by the National Institute for Health Research. G. Chapman None. A.J. Redmond None. H. Xiang None. M. Scott None. M. Richards None. L. Horn None. B. Palmer None. D. Stephensen None.